Formin Homology 2 Domain Containing 3 Variants Associated With Hypertrophic Cardiomyopathy - Wooten, Eric C.; Hebl, Virginia B.; Wolf, Matthew J.; Greytak, Sarah R.; Orr, Nicole M.; Draper, Isabelle; Calvino, Jenna E.; Kapur, Navin K.; Maron, Martin S.; Kullo, Iftikhar J.; Ommen, Steve R.; Bos, J. Martijn; et al. (Circulation. Cardiovascular genetics, 2013)
BACKGROUND—Incomplete penetrance and variable expression of hypertrophic cardiomyopathy (HCM) is well appreciated. Common genetic polymorphisms variants that may affect HCM penetrance and expression have been predicted but are not well established. METHODS AND RESULTS—We performed a case-control genomewide association study to identify common HCM-associated genetic polymorphisms and then asked whether such common variants were more represented in HCM or could explain the heterogeneity of HCM phenotypes. We identified an intronic FHOD3 variant (rs516514) associated with HCM (odds ratio, 2.45; 95% confidence interval, 1.76–3.41; P=1.25×10) and validated this finding in an independent cohort. Next, we tested FHOD3-V1151I (rs2303510), a nonsynonymous variant in partial linkage disequilibrium with rs516514, and we detected an even stronger association with HCM (P=1.76×10). Although HCM patients were more likely to carry these, FHOD3 allele subjects homozygous for FHOD3-1151I had similar HCM phenotypes as carriers of the V1151 allele. FHOD3 expression is increased in the setting of HCM, and both alleles of FHOD3-V1151I were detected in HCM myectomy tissue. Previously, FHOD3 was found to be required for formation of the sarcomere, and here we demonstrate that its fly homolog fhos is required for normal adult heart systolic contraction. CONCLUSIONS—Here we demonstrate the association of a common nonsynonymous FHOD3 genetic variant with HCM. This discovery further strengthens the potential role of gene mutations and polymorphisms that alter the amino acid sequence of sarcomere proteins and HCM.